2012
DOI: 10.4209/aaqr.2011.09.0145
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Air Pollution Emissions from Burning Incense with the Addition of Calcium Carbonate

Abstract: A laboratory-scale study was performed to quantify the pollutant reduction effects from burning incense with the addition of CaCO 3 . Many studies have investigated the effects of burning incense on the quality of surrounding air, focusing primarily on particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs). However, the reduction of PM and PAHs from burning incense has received little attention. In our past study, we investigated nine types of commercially available incense and found that incense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this context, relevant studies have investigated various approaches to incense-related health issues, such as smoke emission reduction [6,13] and ventilation conditions improvement [14]. Though recent scholars have studied the public actions of risk behavior reduction (e.g., tobacco control) [2,39,40], the individual’s perceptual reaction to incense burning receives little attention, which makes it difficult to determine relevant policies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, relevant studies have investigated various approaches to incense-related health issues, such as smoke emission reduction [6,13] and ventilation conditions improvement [14]. Though recent scholars have studied the public actions of risk behavior reduction (e.g., tobacco control) [2,39,40], the individual’s perceptual reaction to incense burning receives little attention, which makes it difficult to determine relevant policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the rising awareness of health issues, nevertheless, studies have indicated that exposure to incense smoke may be linked to carcinogen-related health issues [3,4,5,6,7,8,9,10,11,12]. Though many scholars have exerted efforts to reduce health risks involved in incense burning, such as smoke emission reduction [6,13] and ventilation conditions improvement [14], the behavioral interventions have received little research attention.…”
Section: Introductionmentioning
confidence: 99%